Clinical Outcomes of Diffuse Axonal Injury According to Radiological Grade - Hak-Jae Lee; Hyun-Woo Sun; Jae-Seok Lee; Nak-Joon Choi; Yoon-Joong Jung; Suk-Kyung Hong (Journal of Trauma and Injury)
Purpose Patients with diffuse axonal injury experience various disabilities and have a high cost of treatment. Recent researches have revealed the underlying mechanism and pathogenesis of diffuse axonal injury. This study aimed to investigate the correlation between the radiological grading of diffuse axonal injury and the clinical outcomes of patients. Methods From January 2011 to December 2016, among 294 patients with traumatic brain injury, 44 patients underwent magnetic resonance imaging (MRI). A total of 18 patients were enrolled in this study except for other cerebral injuries, such as cerebral hemorrhage or hypoxic brain damage. Demographic data, clinical data, and radiological findings were retrospectively reviewed. The grading of diffuse axonal injury was analyzed based on patient’s MRI findings. Results For the most severe diffuse axonal injury patients, prolonged intensive care unit (ICU) stay (p=0.035), hospital stay (p=0.012), and prolonged mechanical ventilation (p=0.030) were observed. However, there was no significant difference in healthcare-associated infection rates between MRI grading (p=0.123). Massive transfusion, initial hemoglobin and lactate levels, and MRI gradings were found to be highly significant in predicting the duration of unconsciousness. Conclusions This study showed that patients with high grade diffuse axonal injury have prolonged ICU stays and significantly longer hospital stays. Deteriorated mental patients with high energy injuries should be evaluated to identify diffuse axonal injuries by using an appropriate imaging tool, such as MRI. It will be important to predict the duration of consciousness recovery using MRI scans.